Zakat for The Economy of the Ummah (Case Study in Sihapas Barumun Palas Sub-District, North Sumatra) - Hasibuan, Pendi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Zakat in Islam is one of the pillars of Islam, which is very good for increasing or advancing the economy of the community in particular. If zakat is managed or carried out by professional parties, it will certainly achieve its purpose and be successful. People who are entitled to receive zakat or mustahiq will feel a positive impact if the implementation of this zakat is done properly. Of course, this all depends on the parties who manage the zakat. One of the management styles of this zakat that needs to be developed is productive zakat, namely the management of zakat that is productive and not of a constructive nature. The impact of zakat will be felt by people who mustahiq, namely helping capital so that it helps the community's economy, one of which is alleviating poverty. This research is qualitative and will reveal or describe the data obtained from Lepangan through interviews. The interviews were conducted with people who manage productive zakat in the Sihapas Barumun sub-district, Padang Lawas, North Sumatra. The research conducted at this location has yielded good results. The management of productive zakat in this area has succeeded in increasing the mustahiq's economy or removing them from the poverty line. Zakat managers in this area initially recorded people who were included in the mustahiq category, then provided capital in the form of money, or hwwan.Zakat dalam islam merupakan salah satuvrukun islam yang sangat baik dalam rangka menaikkan atau memajukan perekonomian masyarakat khususnya.zakat ini bila dikelola atau dilalsankan oleh pihak-pihak yang profesional tentu akan mencapai atau tujuan zakat ini akan berhasil.orang-orang yang berhak menerima zakat atau mustahiq akan merasakan dampak positif jika pelaksanaan zakat ini diterpkan dengan baik,tentu ini semuanya tergantung kepada pihak-pihak yang mengelola zakat tersebut. Pengelolaan zakat ini salah satunya yang perlu dikembangkan adalah zakat produktif, yaitunyaÂ pengelolaan zakat yang sifatnya zakat itu untuk produktif bukan yang sifatnya komsuftif.Zakat itu akan dirasakan oleh orang-orang yang mustahiq dampaknya yaitu menolong,modal sehingga membantu perekonomian masyarkat yang salah satunya adalah pengentasan kemiskinan.Penelitian ini sifatnya kualitatif ,yang mana akan mengungkapkan atau mendeskripsikan data yang siperoleh dari lepangan lewat wawancara. Wawancara dilaksanakan kepada orang-orang yang mengelola zakat produktif di kecamatan Sihapas Barumun Padang Lawas Sumatera utara. Penelitian yang dilakukan di lokasi tersebut mendapatkan hasil yang baik .pengelolaan zakat produktif di daerah ini mampau atau berhasil menibgkatkan perekonomian mustahiq atau mengeluarkan mereka dari garis kemiskinan. Pengelola zakat di daerah ini awalnya mendata masyarakat yang masuk dalam kategori mustahiq selanjutnya ada pemberian modal berupa uang atau hwwan.